Efficacy and Safety of Ondansetron versus Metoclopramide Treatment in Infants with Gastroesophageal Reflux Disease: A Comparative Study of Short Trial - Irum Jabeen; Asma Akbar; Shakil Ahmad; Sonia Ilyas; Asmatullah (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To compare the efficacy and safety of ondansetron versus Metoclopramide in infants with gastroesophageal reflux disease (GERD). METHODOLOGY: This single-centre, randomized controlled trial was conducted at the Pediatric Medicine outpatient department, Allama Iqbal Teaching Hospital, Dera Ghazi Khan, from July to December 2024. Infants aged 1–12 months with GERD refractory to conservative management were randomized (1:1) to receive oral Metoclopramide or ondansetron for one week. Eligible infants were enrolled using a simple random sampling technique. Diagnosis was based on clinical history and exclusion of hypertrophic pyloric stenosis by ultrasound. Treatment response (?70% reduction in vomiting episodes and weight preservation/gain) and adverse events were assessed at follow-up. Data were analyzed using SPSS v26.0, with p<0.05 considered statistically significant. RESULTS: Of 284 enrolled infants, 154 (54.2%) were male. The median age was 7.00 (IQR 4.00–10.00) months. Rural residence was noted in 200 (70.4%) infants, and exclusive breastfeeding in 144 (50.7%). A total of 271 infants (95.4%) completed follow-up (Metoclopramide: n=136, ondansetron: n=135). Treatment response occurred in 225 (83.0%) infants, with no significant difference between metoclopramide (79.4%) and ondansetron (86.7%) groups (p=0.112). Adverse events were relatively similar between groups for diarrhea (20.6% vs 22.2%, p=0.743) and lethargy (10.3% vs 11.9%, p=0.683). Warm flushes (5.9%) and constipation (2.2%) were observed only with ondansetron. CONCLUSION: In infants with GERD, ondansetron appears to offer acceptable efficacy, reinforcing its position as a preferred agent where resources permit. Metoclopramide remains an appropriate alternative, particularly in settings where access or cost are significant considerations.